2008
DOI: 10.1152/ajpregu.90406.2008
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in activity of lower urinary tract in response to intravesical acid irritation in decerebrate unanesthetized mice

Abstract: related differences in lower urinary tract (LUT) activity responding to intravesical infusion of diluted acetic acid (A/A, pH 3.0) were investigated during cystometrograms in decerebrate unanesthetized mice. A/A produced a decrease of intercontraction intervals in both female and male animals, and the extent of the decrease in male mice was much less than in female mice [19 Ϯ 5% (P ϭ 0.03) vs. 65 Ϯ 5% (P ϭ 0.03); n ϭ 6 for each], exhibiting a marked difference between the two groups in response to acid irritat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
38
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 54 publications
7
38
0
Order By: Relevance
“…Our new cystometry method appears to minimize the effect of the catheter and may provide a more accurate and reliable analysis of mouse bladder function. In fact, the cystometric VV measured by this new method was more comparable to the spontaneous VV than that reported in previous studies (9,17,23,24). Moreover, this new method enabled us to determine the decrease in BCP that occurs in LPS-induced cystitis, which was not detectable by the conventional cystometry method.…”
Section: Validity Of the New Cystometry Methods With The Catheter Placsupporting
confidence: 67%
See 1 more Smart Citation
“…Our new cystometry method appears to minimize the effect of the catheter and may provide a more accurate and reliable analysis of mouse bladder function. In fact, the cystometric VV measured by this new method was more comparable to the spontaneous VV than that reported in previous studies (9,17,23,24). Moreover, this new method enabled us to determine the decrease in BCP that occurs in LPS-induced cystitis, which was not detectable by the conventional cystometry method.…”
Section: Validity Of the New Cystometry Methods With The Catheter Placsupporting
confidence: 67%
“…In vivo cystometry is a most common method of analyzing bladder function, but it is rather difficult to perform reliably in mice (1). Actually, the cystometric voided volume (VV) of the normal mouse varies widely between 29 and 168 l according to previous reports (9,17,23,24). However, these cystometric VVs are remarkably small compared with mouse spontaneous VVs estimated from voided spots on paper (ranging from 200 to 520 l) (12,16,22).…”
mentioning
confidence: 99%
“…Voiding efficiency (VE; % of bladder volume voided) was estimated as (VV/VT) ϫ 100. Other evaluated parameters were pressure threshold (PT; mmHg) for inducing a voiding contraction, maximal voiding pressure (MVP; mmHg), closing peak pressure (CPP; mmHg), postvoid resting pressure (RP; mmHg), bladder contraction duration (BCD; s), and bladder compliance (BCP; l/mmHg) (18,20). BCP was calculated as the ratio of the infused volume to the pressure difference between two time points at the RP and the PT.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…A recent study (54) revealed sex-specific differences in activity of the lower urinary tract (LUT) responding to intravesical acetic acid (AA) infusion in decerebrate unanesthetized mice. The study demonstrated that female bladders are more sensitive to the noxious stimulation than male bladders, implying an association between sex and bladder sensitivity to irritation.…”
mentioning
confidence: 99%
“…Therefore, this study was conducted in both females and males by intravesically infusing capsazepine, a selective TRPV1 antagonist, to examine the possible involvement of TRPV1 in activity of the LUT in response to AA irritation. Decerebrate unanesthetized mice (54) were used to avoid possible artifacts caused by behavioral responses and movements of awake animals that receive persistent intravesical irritant during cystometry (6,34) and anesthesiainduced suppressions of the LUT activity (27,56,61). Moreover, to facilitate better understanding of the complex autonomic functions, we used detailed cystometric evaluations (54).…”
mentioning
confidence: 99%